2018
DOI: 10.1101/gr.228809.117
|View full text |Cite
|
Sign up to set email alerts
|

ZFX acts as a transcriptional activator in multiple types of human tumors by binding downstream from transcription start sites at the majority of CpG island promoters

Abstract: High expression of the transcription factor ZFX is correlated with proliferation, tumorigenesis, and patient survival in multiple types of human cancers. However, the mechanism by which ZFX influences transcriptional regulation has not been determined. We performed ChIP-seq in four cancer cell lines (representing kidney, colon, prostate, and breast cancers) to identify ZFX binding sites throughout the human genome. We identified roughly 9000 ZFX binding sites and found that most of the sites are in CpG island … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 49 publications
1
62
0
Order By: Relevance
“…All ChIP-seq samples were performed in duplicate according to a previously published protocol [ 57 59 ]. Five micrograms of CTCF antibody (Active Motif #61311) was used to precipitate 20 μg chromatin for 22Rv1, PrEC, RWPE-2, VCaP (rep1) cells, and 10 ul CTCF antibody (Cell Signaling #3418S) were used to precipitate 20 μg chromatin for LNCaP, C4-2B, RWPE-1, VCaP (rep2) cells.…”
Section: Methodsmentioning
confidence: 99%
“…All ChIP-seq samples were performed in duplicate according to a previously published protocol [ 57 59 ]. Five micrograms of CTCF antibody (Active Motif #61311) was used to precipitate 20 μg chromatin for 22Rv1, PrEC, RWPE-2, VCaP (rep1) cells, and 10 ul CTCF antibody (Cell Signaling #3418S) were used to precipitate 20 μg chromatin for LNCaP, C4-2B, RWPE-1, VCaP (rep2) cells.…”
Section: Methodsmentioning
confidence: 99%
“…ZFX can be used as a prognostic biomarker for malignant tumors [ 47 , 50 , 52 ]. ZFX acts as a transcriptional activator in various human malignancies mainly by binding downstream of the transcription initiation site in the CpG island promoter of target genes [ 53 ]. Recent studies have shown that miRNAs affect the biological behavior of tumors by regulating ZFX.…”
Section: Discussionmentioning
confidence: 99%
“…21 ZNF711 and zinc-finger protein X-linked (ZFX) are known to bind to gene promoter regions in the breast cancer cell line MCF7 and participate in transcriptional regulation. 9 However, the specific function and mechanism of ZNF711 in breast cancer cells remain unclear. In this study, the association between ZNF711 expression and clinical characteristics was analyzed in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc-finger proteins are correlated with tumorigenesis and the development of multiple types of human cancers and may be useful as prognostic factors. [4][5][6][7][8][9] ZNF711 is a newly discovered zinc-finger protein involved in the development of neurons. Recent studies have shown that ZNF711 is expressed in BCa cell lines, but its function and regulatory mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%